Pemertahanan bahasa ibu dalam ranah keluarga pada masyarakat suku Bugis di Kepulauan Karimunjawa - Rahim, Asrorur; Chandra, Oktiva Herry; Suryadi, M. (Universitas Mulawarman, 2023)
The purpose of this study is to describe the preservation of the mother tongue in the family sphere in the Bugis community in the Karimunjawa Islands. This research used a descriptive qualitative method. Data were collected using observation and unstructured interviews. Data analysis used Miles and Huberman's theory, the sociolinguistic approach related to preservation, and the language shift by Spolsky and Schiffman. The results of the analysis are presented descriptively. The results of this study indicate the role of the head of the family in regulating the pattern of selection and preservation of the mother tongue in the family of the Bugis ethnic community in the Karimunjawa Islands region. There is a slight difference between ideological patterns related to the process of language preservation in families in young families and non-young families. Young families are more flexible in intervening in the linguistic ideology of their children, while non-young families appear to have strong interventions. The multilingual Bugis community still exists and practices its language and maintains Bugis to communicate in the sphere of daily life, despite being able to use Javanese and Indonesian. Tradition and culture are also important supports for language maintenance in the Bugis community in Karimunjawa.